BOOK REVIEW: THE VALUE OF QUESTIONS IN LET’S TALK TEXTBOOK PUBLISHED BY PAKAR RAYA FOR THE SECOND YEAR STUDENTS OF JUNIOR HIGH SCHOOL AT SLTP N SIAK HULU - Destri Wahyuningsih (JEE (Journal of English Education), 2017)
This research is a book review of questions in "Let's Talk" text book published by Pakar Raya which is used as a textbook for all second years ofjunior high school in Siak Hulu. The questions in textbook is one aspect that influence in teaching learning process and monitoring students learning. Cognitive domain is an ability that is demanded from students to be mastered because it is absolutely a basic for mastering knowledge and intellectual skills. The aims of this research to find the level of questions in "Let's Talk" text book based on Cognitive domain. There are knowledge questions, comprehension questions, applications questions, analysis questions, synthesis questions and evaluation questions. This research is descriptive research using questionnaire as research instrument.